2013
DOI: 10.1021/ja406053b
|View full text |Cite
|
Sign up to set email alerts
|

DNA Tetraplexes-Based Toehold Activation for Controllable DNA Strand Displacement Reactions

Abstract: Most of the dynamic DNA devices are rationally constructed by utilizing toehold-mediated DNA strand displacement reactions. However, such approaches have been mainly limited to the operation with double-stranded hybridization and lack the versatility of DNA scaffold responses for additional levels of controlling DNA strand displacement reactions. Herein, we propose a toehold activation strategy based on the DNA tetraplex (G-quadruplex or i-motif), where the toehold domain is designed by attaching a complementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 54 publications
0
53
0
Order By: Relevance
“…1b and Supplementary Figs. 30-33) 33 . The fluorescence kinetics verified this dynamic process (Fig.…”
Section: And 2 and Supplementarymentioning
confidence: 99%
“…1b and Supplementary Figs. 30-33) 33 . The fluorescence kinetics verified this dynamic process (Fig.…”
Section: And 2 and Supplementarymentioning
confidence: 99%
“…In this design, the binding of aptamer and the target acts as the toehold of the following strand displacement reaction, termed aptamer-toehold, which is an extension of toehold-mediated strand displacement theory. [26][27][28] Fluorescence titration of GDMFs by increased concentrations of ATP is shown in Figure 6C, and the selectivity is shown in Figure S19B. Intracellular ATP imaging is shown in Figure 6D using HeLa cells, giving an obvious green signal from the cytoplasm in the fluorescein isothiocyanate (FITC) channel.…”
Section: Metal-crosslinked Dna Micelle Flaresmentioning
confidence: 99%
“…We demonstrated that the reaction rates can be tuned and controlled dynamically at room temperature through variation of the concentration of Hg 2+ ions [41]. Recently, displacement reaction triggered by functional toeholds formed such as ions [42] and micromolecule [43], has also been investigated. Herein we further utilize the concept of ‘‘metallo-toeholds’’ in which the toehold domains feature C:C mismatched bases.…”
Section: Introductionmentioning
confidence: 99%